Born to fight? Genetics and combat sports - Emerson Franchini (Universidad de León, 2014)
Recently, the influence of genetics on sports performance has received increased attention from many researchers. In combat sports, some investigations have also been conducted. This article's main objective was to review the representation of specific gene polymorphisms in combat sports athletes compared to controls. The following databases were searched: PubMed, Web of Science and SportDiscus. The terms used in this search involved combat sports (boxing, karate, judo, mixed martial arts, taekwondo and wrestling), genes, genetics and candidate genes. Articles published until November 2013 were included if combat sports athletes were considered as a single group (i.e., not mixed with athletes of other sports). Seven studies were found, with two presenting no difference between combat sports athletes and controls, two presenting higher frequencies of candidate genes related to a more endurance-related profile compared to controls, and three where a more power-related gene overrepresentation was found in comparison to controls. Taken together, the initial studies about the genetic characteristics of combat sports athletes are controversial, which is probably due to the mixed (aerobic and anaerobic) characteristic and to the multifactorial performance determinants of these sports.